Advancing Sewage Treatment in India: Challenges, Technology Choices, and Sustainable Strategies - Joshi, Dheeraj (Digital Repository of Theses - SSBM Geneva, 2025)
India faces a growing water crisis exacerbated by rapid urbanization, industrialization, and population growth, leading to increased sewage generation and widespread water pollution. This dissertation investigates the challenges, technology choices, and sustainable strategies for advancing sewage treatment in India, aiming to provide actionable insights for technology applicability, stakeholders opinions considering the views from businesses, policymakers, and investors. Through a mixed-methods approach, including a case study analysis of Padmini VNA Mechatronics Ltd., a TESEI (Technological, Economic, Social, Environmental, and Institutional) analytical framework is developed to assess the complexities of the Indian sewage treatment sector. The mixed method approach follows this way; I first did the literature review on the current status of sewage treatment in India to have a holistic understanding of the wastewater and its treatment in India which gave the insights on technology, policies, how each state and union territories is performing in these aspects along with the exploration of various challenges. Second, I did the case study design considering the sewage treatment plant as base along with technology expansion considering reverse osmosis and ultra filtration units to see how they will perform. In this step, I procured the data from vendors accordingly the life cycle assessments and techno-economic assessments were done briefly. Once, the modelling is done, in the third step, I have explored the various sustainable strategies possible and formulated questions on it to verify whether the wastewater community is interested in this or not. In the fourth step, considering the outcomes from literature review especially the technology options and challenges, case study outcomes with technology additions, and validated expert groups opinion on sustainable strategies a TESEI matrix of challenges is constructed and validated by conducted a survey. Overall, the findings reveal significant gaps in treatment capacity, operational inefficiencies, and limited adoption of advanced and sustainable technologies. Key challenges include aging infrastructure, resource expenditure constraints, corruption, and low public willingness to pay. The research highlights the potential of advanced tertiary treatment systems, resource recovery, and circular economy principles to enhance water quality, reduce environmental impacts, and create economic opportunities. Future research propositions focus on evaluating the performance of existing STPs, promoting decentralized treatment systems, and developing integrated models for sustainable water management in India.